2022
DOI: 10.1038/s42003-022-03590-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-dot-labeled synuclein seed assay identifies drugs modulating the experimental prion-like transmission

Abstract: Synucleinopathies are neurodegenerative disorders including Parkinson disease (PD), dementia with Lewy body (DLB), and multiple system atrophy (MSA) that involve deposits of the protein alpha-synuclein (α-syn) in the brain. The inoculation of α-syn aggregates derived from synucleinopathy or preformed fibrils (PFF) formed in vitro induces misfolding and deposition of endogenous α-syn. This is referred to as prion-like transmission, and the mechanism is still unknown. In this study, we label α-syn PFF with quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…This hypothetical concept is supported by autopsy results in the brains of PD patients who received transplants of fetal mesencephalic tissues more than a decade ago; in these brains, αSYN‐positive LB‐like inclusions were confirmed within donor‐derived neurons 15,16 . Furthermore, the non‐cell‐autonomous spread of αSYN aggregates has been verified via neuronal co‐culture and animal models, which showed that misfolded αSYN released from neurons can transfer to neighboring cells and convert normal physiological αSYN to toxic misfolded species in a prion‐like manner 17–23 . Following its validation, this “prionoid” hypothesis is now widely accepted as a common phenomenon in the pathogenesis of neurodegenerative diseases involving aberrant protein aggregates 24 …”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…This hypothetical concept is supported by autopsy results in the brains of PD patients who received transplants of fetal mesencephalic tissues more than a decade ago; in these brains, αSYN‐positive LB‐like inclusions were confirmed within donor‐derived neurons 15,16 . Furthermore, the non‐cell‐autonomous spread of αSYN aggregates has been verified via neuronal co‐culture and animal models, which showed that misfolded αSYN released from neurons can transfer to neighboring cells and convert normal physiological αSYN to toxic misfolded species in a prion‐like manner 17–23 . Following its validation, this “prionoid” hypothesis is now widely accepted as a common phenomenon in the pathogenesis of neurodegenerative diseases involving aberrant protein aggregates 24 …”
Section: Introductionmentioning
confidence: 79%
“…The proposed mechanism underlying the mode of αSYN aggregate uptake by cells include endocytosis, macropinocytosis, extracellular vesicles, and direct cellular contact via nanotube tunnel 24 . Several studies have highlighted the importance of the endocytic process because low temperature and the genetic and chemical ablation of dynamin, a key determinant for vesicle scission, markedly decrease the internalization of αSYN in cell cultures and animal models 17,20,26 . Studies have sought to determine whether the endocytic uptake of αSYN is receptor‐mediated, because the existence of specific receptors for misfolded αSYN on the cell surface might explain the region‐ and cell‐type‐specific neurodegeneration in synucleinopathies 24,27 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second repurposing candidate is riluzole, which has the ability to reduce the alpha-synuclein protein aggregation seeds [ 45 ]. The current indication for riluzole is amyotrophic lateral sclerosis [ 43 ].…”
Section: Resultsmentioning
confidence: 99%